Pilot study on the impact of HIFU treatment on miRNA profiles in vaginal secretions of uterine fibroids and adenomyosis patients - Wei-Chun Chen; Ting-Chang Chang; Lynn Perera; Mei-Hsiu Cheng; Jun-Jie Hong; Chao-Min Cheng (International Journal of Hyperthermia)
Background High intensity focused ultrasound (HIFU) ablation treatment for uterine fibroids and adenomyosis has been long developed. The aim of this study is to investigate miRNA profile changes in vaginal secretions after HIFU treatment and their clinical relevance.Methods We prospectively collected vaginal secretions samples from 8 patients (1 with adenomyosis and 7 with fibroids) before and after HIFU treatment. RNA was isolated and miRNA profiles were analyzed using next-generation sequencing (NGS) sequencing.Results Our study showed miRNA profile change in vaginal secretion samples after HIFU treatment for uterine fibroids/adenomyosis, with 33 miRNAs upregulated and 6 downregulated overall. In fibroid cases, 31 miRNAs were upregulated and 7 downregulated, while in adenomyosis case, 41 miRNAs were upregulated and 71 downregulated. Four miRNAs (hsa-miR-7977, hsa-miR-155-5p, hsa-miR-191-5p, hsa-miR-223-3p) showed significant differences after HIFU treatment in fibroid cases, except in case 5 with the lowest treatment sonications (425 sonications) and energy input (170000 J). hsa-miR-7977 consistently showed downregulation after HIFU treatment. hsa-miR-155-5p were downregulated in case 4 with lowest treatment efficiency (2439.64 J/cm3), while they were upregulated in other cases. hsa-miR-191-5p and hsa-miR-223-3p were downregulated in cases 4 and 7, with case 7 influenced by high sonication and energy due to multiple fibroids.Conclusions HIFU treatment altered miRNA profiles in fibroids/adenomyosis patients. Notably, hsa-miR-7977, hsa-miR-155-5p, hsa-miR-191-5p, and hsa-miR-223-3p showed significant changes in fibroid cases, except in low-energy treatments. hsa-miR-7977 consistently decreased post-treatment, while hsa-miR-155-5p decreased in the least efficient cases. Further research is needed for validation.